Endogenous PTEN acts as the key determinant for mTOR inhibitor sensitivity by inducing the stress-sensitized PTEN-mediated death axis in KSHV-associated malignant cells - Das, Piyanki; Pal, Sonali; Das, Nilanjana; Chakraborty, Koushik; Chatterjee, Koustav; Mal, Sudipa; Choudhuri, Tathagata (Frontiers in Molecular Biosciences, 2023)
As a part of viral cancer evolution, KSHV-infected human endothelial cells exert a unique transcriptional program via upregulated mTORC1 signaling. This event makes them sensitive to mTOR inhibitors. Master transcriptional regulator PTEN acts as the prime regulator of mTOR and determining factor for mTOR inhibitory drug resistance and sensitivity. PTEN is post-translationally modified in KSHV-associated cell lines and infected tissues. Our current study is an attempt to understand the functional role of upstream modulator PTEN in determining the sensitivity of mTOR inhibitors against KSHV-infected cells in an in vitro stress-responsive model. Our analysis shows that, despite phosphorylation, endogenous levels of intact PTEN in different KSHV-infected cells compared to normal and non-infected cells are quite high. Genetic overexpression of intact PTEN showed functional integrity of this gene in the infected cells in terms of induction of a synchronized cell death process via cell cycle regulation and mitochondria-mediated apoptosis. PTEN overexpression enhanced the mTOR inhibitory drug activity, the silencing of which hampers the process against KSHV-infected cells. Additionally, we have shown that endogenous PTEN acts as a stress balancer molecule inside KSHV-infected cells and can induce stress-sensitized death program post mTOR inhibitor treatment, lined up in the ATM-chk2-p53 axis. Moreover, autophagic regulation was found as a major regulator in mTOR inhibitor-induced PTEN-mediated death axis from our study. The current work critically intersected the PTEN-mediated stress balancing mechanism where autophagy has been utilized as a part of the KSHV stress management system and is specifically fitted and switched toward autophagy-mediated apoptosis directing toward a therapeutic perspective.